Application of discriminate analysis to assess the impact of accreditation in health in the profitability indicators in Colombia - Morelos Gómez, José; Fontalvo Herrera, Tomás J.; Vergara Schmalbach, Juan Carlos (Universidad y Salud, 2013)
Introduction: In this research paper, the impact on the profitability indicators of health institutions accredited during 2008 and 2010 was assessed. A multivariate discriminant analysis in 20 accredited health organizations was done. These institutions presented their financial status at the Health Superintendence. Methods: To achieve this, financial indicators were defined and calculated to explain its membership, discrimination and evolution. Results: It was proved by means of discriminant functions that there are significant differences for Gross Margin indicator (GM); and by analysis of means, that accreditation positively impacts indicators Net Margin (MN) and Operating Margin (MO), which also evolved. Conclusion: It could be concluded that the model can predict and facilitate decision making for those responsible of these processes, so they can develop actions that contribute to improving the financial status of the accredited health institutions.